Nutritional Assessment Among Post COVID-19 and Non COVID-19 Elderly Population in Jodhpur, India: A Cross Sectional Study - Yadav, Sakshi R.; Singh, Madhu Bala; Meena, Sumitra; Vyas, Khushboo; Yadav, Vipul R.; Sharma, Deepak; Yadav, Ranjeet S. (Annals of Arid Zone, 2023)
A cross-sectional study was carried out in south-west covering areas of Pal,Madhuban, Sangariya primary health centers of Jodhpur city in order to assess thenutritional status of post COVID-19 and non COVID-19 elderly population using theMini Nutritional Assessment (MNA) techniques. All the subjects were categorized intonon-malnutrition (MNA ≥ 24), risk of malnutrition (MNA 17-23.5) and malnutrition(MNA score < 17) groups using MNA score. A total of 200 elderly subjects including100 each for post COVID-19 and non COVID-19 categories representing 56% male and44% females were included in the study. Further these elderly subjects were dividedinto two age groups belong to 60-67 years age (early geriatric) and 68-85 years age (lategeriatric). The results revealed that about 61 (67.9% males & 52.3% Females) and 71(66.1% Males & 77.3% Females) percent belongs to early geriatric group, and 39 (32.1%Males & 47.7% Females) and 29 (33.9% Males & 22.7% Females) percent belongs to lategeriatric group in post COVID-19 and non COVID-19 categories, respectively. Religionwise, 95 and 99% subjects were belongs to Hindu in post COVID-19 and non COVID-19subjects, respectively. About 29 (25% Males & 34% Females) and 12 (19.6% Males &2.3% Females) percent belongs to general caste, 51 (53.6% Males & 47.7% Females) and60 (64.3% Males & 54.5% Females) percent belongs to OBC community both in postCOVID-19 and non COVID-19 categories, respectively. Rest were belongs to SC andST in respective category. Overall, the nutritional status of elderly is not satisfactory inboth the groups. The percentage of malnutrition observed significantly higher amongpost COVID-19 (18%) than non COVID-19 (15%) elderly population. Further, males weresuffered more than females in terms of malnutrition both in post COVID-19 (35.7%) andnon COVID-19 (48.2%) groups. Generally, the prevalence of malnutrition was higher inpost COVID-19 subjects. However, higher prevalence of malnutrition (2 to 5%) as wellas risk of malnutrition (2 to 20%) was observed in early geriatric than late geriatricgroup both in post COVID-19 and non COVID-19 categories.